Do emotions help or hurt decision making? : a hedgefoxian perspective - Vohs, Kathleen D.; Baumeister, Roy F.; Loewenstein, George (Russell Sage Foundation, 2007)
"Philosophers have long tussled over whether moral judgments are the products of logical reasoning or simply emotional reactions. From Jane Austen's Sense and Sensibility to the debates of modern psychologists, the question of whether feeling or sober rationality is the better guide to decision making has been a source of controversy. In Do Emotions Help or Hurt Decision Making? Kathleen D. Vohs, Roy F. Baumeister, and George Loewenstein lead a group of psychologists and economists in exploring the empirical evidence on how emotions shape judgments and choices." "Researchers on emotion and cognition have staked out many extreme positions: viewing emotions as either the driving force behind cognition or its side effect, either an impediment to sound judgment or a guide to wise decisions. The contributors to Do Emotions Help or Hurt Decision Making? provide a richer perspective, exploring the circumstances that shape whether emotions play a harmful or helpful role in decisions."--Jacket